2005
DOI: 10.1515/jpem.2005.18.9.897
|View full text |Cite
|
Sign up to set email alerts
|

Near Normalisation of Lumbar Spine Bone Density in Young Women with Osteopenia Recovered from Adolescent Onset Anorexia Nervosa: A Longitudinal Study

Abstract: To investigate the effect of the progression of adolescent onset anorexia nervosa (AN) on bone parameters we followed two cohorts (Disease cohort and recovered cohort) of adolescents for a total of 5.2 years. In the 'Disease' cohort (n = 18), lumbar spine bone density (BMD) was reduced by 0.6 SD after 0.8 years of disease and was reduced a further 1.0 SD after a total 2.5 years of disease (p < 0.001). At the third lumbar vertebra there was bone loss (-3.7%, p < 0.05) resulting in reduced volumetric BMD (-5.1%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
1
20
1
1
Order By: Relevance
“…(38) Further, in girls recovering from anorexia nervosa, while bone-mass gains were positively associated with weight gain, even those who had established a normal weight did not increase bone mass to normal levels. (39)(40)(41)(42) A previous study by Lucas and colleagues that compared adolescent runners and nonrunners found no differences between runners (n ¼ 15) and nonrunners (n ¼ 27) in body weight or BMD at each bone site, and it therefore was concluded that runners' exercise activity did not negatively affect their bone mass. (43) Although the results of that study might appear contradictory to our findings, the runners in that study sample ranged in age from 12 to 14 years.…”
Section: Discussionmentioning
confidence: 90%
“…(38) Further, in girls recovering from anorexia nervosa, while bone-mass gains were positively associated with weight gain, even those who had established a normal weight did not increase bone mass to normal levels. (39)(40)(41)(42) A previous study by Lucas and colleagues that compared adolescent runners and nonrunners found no differences between runners (n ¼ 15) and nonrunners (n ¼ 27) in body weight or BMD at each bone site, and it therefore was concluded that runners' exercise activity did not negatively affect their bone mass. (43) Although the results of that study might appear contradictory to our findings, the runners in that study sample ranged in age from 12 to 14 years.…”
Section: Discussionmentioning
confidence: 90%
“…Duration of observation may be a factor as other studies have reported near normal bone size and volumetric BMD with recovery. 69,102 A recent longitudinal Australian study demonstrated normalisation of volumetric lumbar spine BMD in adolescent-onset disease after 2.7 years of recovery. 102 Bone mass and volume at the third lumbar vertebrae increased by 20 and 14%, respectively.…”
Section: Weight Restoration With Resumption Of Mensesmentioning
confidence: 99%
“…The discipline of endocrinology has led the field, through the understanding of the hormonal events of puberty and the studies of the initiation of puberty 11 and longitudinal bone acquisition studies. 12 The absence of easy access to relevant animal models of puberty for research is important, with primates being an obvious but costly choice. In addition, no animal model can reproduce many aspects of human adolescence, including the increasing divide between the timing of puberty and the duration of adolescence.…”
Section: Introductionmentioning
confidence: 99%